1995
DOI: 10.1152/jn.1995.74.1.457
|View full text |Cite
|
Sign up to set email alerts
|

Vectorial coding of movement: vision, proprioception, or both?

Abstract: 1. Subjects were asked to point toward visual targets without visual reafference from the moving hand in two conditions. In both conditions the pointing fingertip was viewed only before movement onset. 2. In one condition, the pointing fingertip was viewed through prisms that created a visual displacement without altering the view of the target. In another experimental condition, vision of the fingertip was not displaced. Comparison of these two conditions showed that virtually shifting finger position before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
2
4

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 255 publications
(162 citation statements)
references
References 0 publications
8
145
2
4
Order By: Relevance
“…Alternatively, the motor system could use a different model of the body from those involved in perception and cognition. Clearly, position sense does not rely on proprioceptive information alone, but supplements this with vision (29,30) and efferent copies of motor commands (31). Motor learning might involve correcting a distorted underlying model with these additional inputs, analogous to adaptive changes following exposure to visually distorting prisms (32) or surgical elongation of limbs (33).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the motor system could use a different model of the body from those involved in perception and cognition. Clearly, position sense does not rely on proprioceptive information alone, but supplements this with vision (29,30) and efferent copies of motor commands (31). Motor learning might involve correcting a distorted underlying model with these additional inputs, analogous to adaptive changes following exposure to visually distorting prisms (32) or surgical elongation of limbs (33).…”
Section: Discussionmentioning
confidence: 99%
“…Human sensorimotor performance often seems introspectively to be dominated by vision, and proprioception appears to play a minor role. However, quantitative studies have shown that both contribute to movement control and that the relative contribution of each is determined by the relative reliability of the information provided by each modality about different aspects of the task (Rossetti et al, 1995;van Beers et al, 1999van Beers et al, , 2002Ernst and Banks, 2002;Sabes, 2003, 2005;Saunders and Knill 2003, 2004Bagesteiro et al, 2006;Sarlegna and Sainburg, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, both visual and proprioceptive sensors often simultaneously encode arm position (Cohen and Andersen, 2000;Rossetti et al, 1995). Both visual and auditory channels may encode location of an object.…”
mentioning
confidence: 99%